Reversing T-cell exhaustion in immunotherapy: a review on current approaches and limitations. (4th May 2021) - Tabana, Yasser; Moon, Tae Chul; Siraki, Arno; Elahi, Shokrollah; Barakat, Khaled
ABSTRACT: Introduction :T cell functions are altered during chronic viral infections and tumor development. This is mainly manifested by significant changes in T cells' epigenetic and metabolic landscapes, pushing them into an 'exhausted' state. Reversing this T cell exhaustion has been emerging as a 'game-changing' therapeutic approach against cancer and chronic viral infection. Areas covered :This review discusses the cellular pathways related to T cell exhaustion, and the clinical development and possible cellular targets that can be exploited therapeutically to reverse this exhaustion. We searched various databases (e.g. Google Scholar, PubMed, Elsevier, and other scientific database sites) using the keywords T cell exhaustion, T cell activation, co-inhibitory receptors, and reversing T cell exhaustion. Expert opinion :The discovery of the immune checkpoints pathways represents a significant milestone toward understanding and reversing T cell exhaustion. Antibodies that target these pathways have already demonstrated promising activities in reversing T cell exhaustion. Nevertheless, there are still many associated limitations. In this context, next-generation alternatives are on the horizon. This includes the use of small molecules to block the immune checkpoints' receptors, combining them with other treatments, and identifying novel, safer and more effective immunotherapeutic targets.